Effect of heater geometry and cavity volume on the sensitivity of a thermal convection-based tilt sensor. (5th April 2018) - Han, Maeum; Kim, Jae Keon; Kong, Seong Ho; Kang, Shin-Won; Jung, Daewoong
Abstract: This paper reports a micro-electro-mechanical-system (MEMS)-based tilt sensor using air medium. Since the working mechanism of the sensor is the thermal convection in a sealed chamber, structural parameters that can affect thermal convection must be considered to optimize the performance of the sensor. This paper presents the experimental results that were conducted by optimizing several parameters such as the heater geometry, input power and cavity volume. We observed that an increase in the heating power and cavity volume can improve the sensitivity, and heater geometry plays important role in performance of the sensor.